COVID-19 outbreak lockdown and its impacts on marketing of horticultural produces in Zimbabwe - Parwada, C. (International Journal of Horticultural Science, 2020)
Coronavirus disease of 2019 (COVID-2019) outbreak resulted to a global health problem. Lockdown was one of the common options suggested to curb the pandemic. Horticultural produces are perishable so delayed post-harvest marketing cause losses. This study aimed at evaluating the marketing of horticultural produces and farmers’ level of preparedness during the COVID-19 lockdown. A self-administered questionnaire was posted online from April 7 to May 7, 2020 the first month of COVID-19 lockdown in Zimbabwe (began on March 30, 2020). The study targeted horticultural farmers around Harare peri-urban and had 300 respondents. Data on sociodemographic, farmers’ behavior, awareness and attitude toward marketing and desire to minimize post-harvest losses was obtained. Frequency counts and percentages were determined. Chi-square tests on independent variables were done to test associations with demographics using SPSS version 8. There were significant (P35%) produce sale leftovers at the markets and spoilage during than prior the COVID-19 lockdown. The lockdown resulted to low sales and most farmers were unprepared for any crisis during the marketing stage of their production. The research contributed to an understanding of how a crisis situation influence marketing of horticultural produce and raises awareness regarding post-harvest losses. A qualitative study is recommended as a follow-up of this work.